2021
DOI: 10.9758/cpn.2021.19.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Prescribing Clozapine in the Era of COVID-19: A Review Focused on Immunological Implications

Abstract: The global COVID-19 pandemic has disrupted every aspect of the healthcare system. Apart from the issues surrounding COVID-19 itself, care for existing patients has met many challenges. One such challenge is caring for patients who are on clozapine treatment and have been confirmed positive for COVID-19. Schizophrenia has been considered to have a deep connection with the immune system, and clozapine can induce further changes in this system. COVID-19 can ravage the compromised immune system and aggravate tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 100 publications
2
9
0
Order By: Relevance
“…These inflammatory states can aggravate morbidity from COVID-19 infection, and the immunosuppressive effects of clozapine may decrease the defensive capacity of the host. 36 In addition to our main objective, our search also found some interesting results regarding clozapine and COVID-19 vaccination. One study including 139 patients showed that clozapine blood levels have significantly increased after the second COVID-19 vaccination and changes in WBC count were limited to mild granulocytopenia, moderate granulocytopenia, and leukocytopenia.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These inflammatory states can aggravate morbidity from COVID-19 infection, and the immunosuppressive effects of clozapine may decrease the defensive capacity of the host. 36 In addition to our main objective, our search also found some interesting results regarding clozapine and COVID-19 vaccination. One study including 139 patients showed that clozapine blood levels have significantly increased after the second COVID-19 vaccination and changes in WBC count were limited to mild granulocytopenia, moderate granulocytopenia, and leukocytopenia.…”
Section: Resultsmentioning
confidence: 87%
“…These inflammatory states can aggravate morbidity from COVID-19 infection, and the immunosuppressive effects of clozapine may decrease the defensive capacity of the host. 36…”
Section: Resultsmentioning
confidence: 99%
“…First, the immunosuppressive effect of clozapine may render a patient more susceptible to COVID-19 (de Leon et al ., 2020). Second, clozapine may exacerbate inflammation and increase the risk of cytokine storms (Jeong and Kim, 2021). Third, since the released cytokines impede the synthesis and action of cytochrome P450 enzymes, clozapine concentrations may soar, leading to sudden toxicity (Cranshaw and Harikumar, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…What is more unsettling is that the elevated ANC might indicate an over-activated cytokine network. Since clozapine has a significant effect on the cytokine network, there is concern that it may increase the likelihood of a cytokine storm, potentially worsening the prognosis (Roge et al ., 2012; Jeong and Kim, 2021). Fortunately, a recent review concluded that there is insufficient evidence that clozapine leads to a worse outcome (Giles et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, the COVID-19 pandemic had an important negative impact on clozapine treatment, mainly because of its administration protocol (initiation, titration, and monitoring), and side effects in patients with COVID-19 infection. 10,11 During the pandemic, studies have shown difficulties in the administration of long-acting injectable antipsychotics (LAIs) 12,13 as well as the unfavorable effects of switching from LAIs to oral antipsychotics. 14 Accumulating evidence indicates that antipsychotics may have a protective effect against SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%